Women's experiences of street trading in Cape Town and its impact on their well-being - Sassen, Sharyn Ruth (Department of Health and Rehabilitation Sciences, 2015)
Street trading forms a large subsection of South Africa's informal economic activity, creating opportunity for self-employment and sustaining livelihoods (Mitullah, 2003; Skinner, 2008). Yet, street traders face various barriers including societal marginalization and pervasive poverty, threatening their well-being. The scarcity of occupational therapy literature around informal economy occupations limits the profession's understanding about what engagement in such occupations entails. While available literature around work in the informal economy emphasises economic contributions to development, there is limited evidence that informal business owners effectively escape vulnerability. From an occupational perspective, little is known about how these occupations are experienced and their implications for well-being. This study will inform contextually relevant conceptions of participation in the informal economy occupation of street trade, providing necessary knowledge for social and political practices of occupational therapy. The study aimed to describe women street traders' experiences of street trading and, how they perceived these related to their well-being. The objectives were to identify personal and external factors that promoted or hindered their well-being whilst engaged in street trading. An ethnographic inquiry was carried out with four women street traders identified through purposive recruitment. It involved semi-structured and photo elicitation interviews, and participant observation. Interviews were audio recorded and transcribed for inductive and thematic cross case analysis and field notes were made following interviews and participant observation. One theme and three categories emerged in the findings. The theme, 'Togetherness: steering against the current towards a better life", revealed the impact of interpersonal connectedness as participants attempted to steer towards valued lives against various barriers. The first category, 'Taking the helm', described the women's actions to determine valued livelihoods. 'Facing tough conditions' detailed the personal and external barriers they encountered while attempting to direct their lives towards positive outcomes through street trading. The third category, 'We're in the same boat' demonstrated the significance and the positive and negative impact of interpersonal connectedness for street traders. Conclusively, the study revealed how the contextually situated nature of this occupation translated to nuanced and fluid experiences of wellbeing in street trading, where well-being was deeply tied to valued social connectedness and significance of collective well-being.